Red‐ and Far‐Red‐Emitting Zinc Probes with Minimal Phototoxicity for Multiplexed Recording of Orchestrated Insulin Secretion. Issue 49 (15th September 2021) - Zhang, Junwei; Peng, Xiaohong; Wu, Yunxiang; Ren, Huixia; Sun, Jingfu; Tong, Shiyan; Liu, Tianyan; Zhao, Yiwen; Wang, Shusen; Tang, Chao; Chen, Liangyi; Chen, Zhixing
Abstract: Zinc biology, featuring intertwining signaling networks and critical importance to human health, witnesses exciting opportunities in the big data era of physiology. Here, we report a class of red‐ and far‐red‐emitting Zn 2+ probes with K d values ranging from 190 nM to 74 μM, which are particularly suitable for real‐time monitoring the high concentration of Zn 2+ co‐released with insulin during vesicular secretory events. Compared to the prototypical rhodamine‐based Zn 2+ probes, the new class exploits morpholino auxochromes which eliminates phototoxicity during long‐term live recording of isolated islets. A Si‐rhodamine‐based Zn 2+ probe with high turn‐on ratio (>100), whose synthesis was enabled by a new route featuring late‐stage N‐alkylation, allowed simultaneous recording of Ca 2+ influx, mitochondrial signal, and insulin secretion in isolated mouse islets. The time‐lapse multicolor fluorescence movies and their analysis, enabled by red‐shifted Zn 2+ and other orthogonal physiological probes, highlight the potential impact of biocompatible fluorophores on the fields of islet endocrinology and system biology. Abstract : We synthesized a new class of red‐ and far‐red‐emitting Zn 2+ probes with minimal phototoxicity, μM affinities and high turn‐on ratios. Tailored for 4D, long‐term and multiple‐color recording of Zn 2+ /insulin co‐secretion in β‐cells and islets, the new probes promise to unveil the spatial‐temporal regulation of islet endocrinology.